(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2007)
This document contains the report of the IOC/FAO/IOTC. Symposium anf Workshop to Strengthen Port State Measure in the Indian Ocean held in Port Louis, Mauritius, from 18 to 22 June 2007. Participant included representatives from gorvernments, industry, regional fisheries management organizations and civil society.
Keywords: Commercial fisheries,Thủy sản thương mại; Indian Ocean,Vùng biển Ấn Độ